Dissociation protocols influence the phenotypes of lymphocyte and myeloid cell populations isolated from the neonatal lymph node - DaMata, Jarina P.; Zelkoski, Amanda E.; Nhan, Paula B.; Ennis, Katherine H. E.; Kim, Ji Sung; Lu, Zhongyan; Malloy, Allison M. W. (Frontiers in Immunology, 2024)
with age-specific immune responses. Lymph nodes (LN) are critical tissue sites to quantify and define these differences. Advances in flow cytometry have enabled more multifaceted measurements of complex immune responses. Tissue processing can affect the immune cells under investigation that influence key findings. To understand the impact on immune cells in the LN after processing for single-cell suspension, we compared three dissociation protocols: enzymatic digestion, mechanical dissociation with DNase I treatment, and mechanical dissociation with density gradient separation. We analyzed cell yields, viability, phenotypic and maturation markers of immune cells from the lung-draining LN of neonatal and adult mice two days after intranasal respiratory syncytial virus (RSV) infection. While viability was consistent across age groups, the protocols influenced the yield of subsets defined by important phenotypic and activation markers.Moreover, enzymatic digestion did not show higher overall yields of conventional dendritic cells and macrophages from the LN. Together, our findings show that the three dissociation protocols have similar impacts on the number and viability of cells isolated from the neonatal and adult LN.However, enzymatic digestion impacts the mean fluorescence intensity of key lineage and activation markers that may influence experimental findings.